A novel endovascular treatment for true ophthalmic aneurysms: A case report - Furst, Taylor; Mattingly, Thomas K.; Williams, Zoë R.; Schartz, Derrek; Bender, Matthew T. (Frontiers in Ophthalmology, 2022)
Introduction Cerebral aneurysms located along the internal carotid artery at the origin of the ophthalmic artery can be treated through open surgery or endovascular technique. The former affords more certainty of aneurysm obliteration, while the latter poses less risk to vision. Flow diversion is an increasingly accepted treatment for side-wall carotid aneurysms, although location at the branch point of the ophthalmic artery is known to moderate occlusion outcomes. Case presentation We present a case of a middle-aged female patient with a morphologically irregular 4-mm ophthalmic artery aneurysm (OphA) and a smaller superior hypophyseal artery (SHA) aneurysm whose successful and uncomplicated obliteration by flow diversion with adjunctive coiling was predicted via a balloon test occlusion (BTO). BTO was employed prior to stent placement to confirm a) ophthalmic artery distal collateralization with external carotid artery (ECA) branches and b) preserved arterial flow in the retina visualized via fundoscopy. At 1 year following angiography, the patient had no postoperative deficits and benefitted from complete occlusion of the OphA and SHA. Conclusion OphAs constitute a complex surgical disease that is historically associated with high visual morbidity. We present a novel advanced endovascular technique of BTO followed by flow diversion with adjunctive coiling that successfully obliterated an OphA while preserving vision.